Evaluation of the Gold Coast Integrated Care for patients with chronic disease or high risk of hospitalisation through a non-randomised controlled clinical trial: a pilot study protocol. Issue 6 (2nd July 2017) - Scuffham, Paul A; Mihala, Gabor; Ward, Lauren; McMurray, Anne; Connor, Martin
Abstract : Introduction: Chronic diseases are the leading cause of illness, disability and death in Australia. The prevalence and associated health expenditure are projected to soar. There is no 'whole system' approach to healthcare in Australia. To overcome this fragmentation, the Gold Coast Hospital and Health Service (GCHHS) is developing a new model known as Gold Coast Integrated Care (GCIC). To evaluate GCIC a 4-year pilot trial commenced in March 2015. This protocol paper describes the evaluation of GCIC. Methods and analysis: A pragmatic non-randomised controlled clinical trial is conducted to test the hypothesis that GCIC will result in improved health and well-being at no additional cost to the healthcare system. Using a mixed methods approach, impact, outcome and process evaluations will be undertaken to assess the effectiveness and acceptability, including the balance of costs between primary and public secondary care sectors, staff and training requirements, clinical service delivery, and trial implementation. Fifteen general practices have agreed to deliver GCIC. One thousand five hundred of their adult patients with treated chronic diseases, high risk of hospitalisation or healthcare utilisation were recruited to the intervention arm. Approximately 3000 patients not associated with the participating general practices were identified as controls using propensity matching which will provide service utilisation and disease data for usual care. Baseline data and follow-up observations are collected annually until the end of 2018. Quantitative analyses will measure patient healthcare costs, utilisation of health services, and health outcomes, and general practice clinical service delivery according to clinical guidelines (number of foot exams, HbA1c tests). Qualitative analyses will focus on patient and staff experiences, satisfaction, engagement and implementation of the programme as planned. Ethics and dissemination: Approval was received from the GCHHS and Griffith University. The study is registered with the Australian New Zealand Clinical Trial Registry (ACTRN12616000821493). Findings will be communicated via yearly reports to funding bodies and scientific publications. Trial registration number: ACTRN12616000821493; Pre-results.